The Influence of Emotional Intelligence on Coping Skills - Yevchenko, Iryna; Masliuk, Andrii; Myronets, Serhii; Dubinina, Kateryna; Ortikova, Nataliia (International Journal of Statistics in Medical Research, 2025)
Background: The relevance of the study is determined by the interest in studying the influence of emotional intelligence (EI) on stress resistance, which is of great importance in view of numerous stress factors. Objective: The aim of the study is to determine the influence of EI on coping skills and the choice of coping strategies. Methods: The study employs a test method (Mayer-Salovey-Caruso Emotional Intelligence Test (MSCEIT), Holmes-Rahe Stress Inventory). The Coping Strategies Questionnaire (CSQ) was also used. The results were processed using statistical methods (mean, range, mode and median, the Mann-Whitney U test, Pearson correlation coefficient (PCC)). The factor analysis was carried out. Results: More pronounced emotion regulation (weight 0.53) have been found in men, while women better recognize emotions (weight 0.45). The correlation between the level of EI and adaptive strategies is confirmed: high EI reduces the negative cumulative effect of stress (M = 55 in a group with high EI). High EI is related to active stress strategies, such as planning and seeking social support, confirming its role as a protective factor. Conclusion: It can be argued that the high EI significantly reduces the frequency, intensity of stress and its impact, facilitating adaptive strategies for overcoming it. Further studies may focus on the influence of EI on stress resistance in different age and cultural groups, as well as on long-term effects in the context of professional stress.